ANALISIS POTENSI MEDIA PEMBELAJARAN CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD - Siti Aminah; Sita Isna Malyuna; Sumadi (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT The integration of digital learning media has created new opportunities to improve science and social science (IPAS) instruction in elementary schools, particularly where students' learning outcomes remain unsatisfactory. Among the available platforms, Canva has attracted increasing attention for its ability to present instructional content through visually engaging and interactive designs. This study investigates its educational contribution by synthesizing evidence from previous research using a descriptive qualitative approach based on a literature review. Seven scholarly articles were retrieved from Google Scholar using the keywords "Canva teaching aids," "IPAS learning achievement," and "elementary school learning." The selected publications were examined through a systematic process of identification, categorization, and synthesis to develop a comprehensive understanding of Canva's role in IPAS learning. The findings reveal a consistent pattern across the reviewed studies, indicating that Canva promotes greater student motivation and active participation during classroom instruction. Evidence from two experimental studies further demonstrates substantial improvement in fourth-grade students' cognitive achievement, with average scores increasing from 50.00–54.67 before the intervention to 80.00–85.17 after Canva-assisted learning. The visual representation and interactive presentation of learning materials also facilitate students' understanding of abstract concepts by making them more concrete, aligning with the cognitive characteristics of learners in the concrete operational stage. These findings suggest that Canva holds considerable promise as an innovative instructional medium for creating more meaningful, engaging, and effective IPAS learning experiences in elementary education. ABSTRAK Perkembangan media digital membuka peluang untuk memperkaya pembelajaran IPAS di sekolah dasar, terutama ketika capaian belajar siswa masih menunjukkan hasil yang belum optimal. Salah satu media yang banyak dimanfaatkan adalah Canva karena memungkinkan penyajian materi melalui perpaduan teks, gambar, dan desain visual yang lebih komunikatif. Untuk memahami kontribusinya terhadap pembelajaran, penelitian ini menyusun sintesis temuan dari berbagai publikasi ilmiah menggunakan pendekatan kualitatif deskriptif berbasis studi pustaka. Sebanyak tujuh artikel yang diperoleh melalui Google Scholar dengan kata kunci "alat peraga Canva", "prestasi belajar IPAS", dan "pembelajaran sekolah dasar" dipilih sebagai sumber analisis, kemudian ditelaah melalui tahapan identifikasi, klasifikasi, dan sintesis sehingga diperoleh gambaran yang komprehensif. Hasil kajian menunjukkan pola yang relatif konsisten bahwa pemanfaatan Canva tidak hanya meningkatkan motivasi dan keterlibatan siswa selama proses pembelajaran, tetapi juga berdampak pada peningkatan capaian kognitif. Pada dua penelitian eksperimen yang dianalisis, rata-rata hasil belajar siswa kelas IV meningkat dari kisaran 50,00–54,67 menjadi 80,00–85,17 setelah pembelajaran memanfaatkan Canva. Penyajian konsep melalui visual interaktif membantu mengonkretkan materi yang bersifat abstrak sehingga lebih sesuai dengan karakteristik berpikir siswa sekolah dasar. Dengan demikian, Canva menunjukkan potensi yang kuat sebagai media pembelajaran inovatif untuk mendukung pembelajaran IPAS yang lebih efektif, bermakna, dan berorientasi pada peningkatan hasil belajar.